2010
DOI: 10.1016/j.visres.2010.06.008
|View full text |Cite
|
Sign up to set email alerts
|

Nature of the refractive errors in rhesus monkeys (Macaca mulatta) with experimentally induced ametropias

Abstract: We analyzed the contribution of individual ocular components to vision-induced ametropias in 210 rhesus monkeys. The primary contribution to refractive-error development came from vitreous chamber depth; a minor contribution from corneal power was also detected. However, there was no systematic relationship between refractive error and anterior chamber depth or between refractive error and any crystalline lens p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
1
5

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 19 publications
(24 citation statements)
references
References 111 publications
1
17
1
5
Order By: Relevance
“…A review paper on the role of the lens in refractive development concluded that “its participation is non-existent or minimal at best”. 29 This agrees with the finding of no association between refractive error and lens thickness in 210 rhesus monkeys, 30 although it should be noted that most of the monkeys were younger than the children tested in the current study even when age was adjusted for the difference between monkey and human years. Another caveat is that most of the experiments using animals lasted for relatively short periods of time and changes in the lens may take longer to appear.…”
Section: Discussionsupporting
confidence: 90%
“…A review paper on the role of the lens in refractive development concluded that “its participation is non-existent or minimal at best”. 29 This agrees with the finding of no association between refractive error and lens thickness in 210 rhesus monkeys, 30 although it should be noted that most of the monkeys were younger than the children tested in the current study even when age was adjusted for the difference between monkey and human years. Another caveat is that most of the experiments using animals lasted for relatively short periods of time and changes in the lens may take longer to appear.…”
Section: Discussionsupporting
confidence: 90%
“…However for this population of esotropic monkeys, which does not include many of the esotropic monkeys with high degrees of anisometropia, the interocular differences in vitreous chamber only explained 13% of the variance in the degree of anisometropia. The resulting correlation was much weaker than that typically observed in monkeys with vision-induced refractive errors (Arumugam, Hung, To, Holden & Smith III, 2014, Qiao-Grider, Hung, Kee, Ramamirtham & Smith III, 2010, Smith III et al, 2012). In contrast, in the prism-reared macaques, the observed anisometropias were strongly correlated with interocular differences in vitreous chamber depth (Figure 11B; r 2 = 0.77).…”
Section: Resultscontrasting
confidence: 69%
“…1C & D). In both form deprivation myopia (FDM) and negative lens-induced myopia (LIM), there are minimal changes in corneal shape or in the power of the crystalline lens (Pickett-Seltner et al, 1987; Qiao-Grider et al, 2010; Schaeffel et al, 1988; Siegwart, Jr. and Norton, 1998). …”
Section: Animal Studiesmentioning
confidence: 99%